Surface elevation changes in an estuarine mangrove forest in Vanga, Kenya: Implications for management and mitigation of sea-level rise - Kimeli, Amon Kibiwot; Cherono, Shawlet; Baya, Patience; Mathinji, Margaret; Okello, Judith Auma; Koedam, Nico; Westphal, Hildegard; Kairo, James Gitundu (Frontiers in Marine Science, 2022)
Mangrove ecosystems are often called “makers of land” due to their ability to promote deposition, trap, and augment sediments. Accurate location- and region-specific elevation information is required to assess and mitigate threats to mangroves caused by their vulnerability to sea-level rise. The provision of land building services by mangroves is primarily sediment-dependent. It is therefore influenced by local factors, including sediment availability and supply. In the present study from Kenya, we measured and examined the variations in surface elevation in mangroves at variable distances from the creek channel using a combination of surface-elevation tables and horizon markers for three years. Elevation changes varied with distance from the creek channel (p < 0.05), with both surface loss and gains recorded. Elevation changes varied between -80 mm (most significant subsidence) and 42 mm (highest accretion) in stations closer to the creek, while farther from the creek (~200 m away), elevation changes ranged between -68 mm (most significant subsidence) and 29 mm (highest accretion). However, net surface elevation changes over the three years showed that shallow subsidence occurred in both stations closer to the creek (-45 ± 7.2 mm) and those farthest from the creek (-20 ± 7.1 mm). At the same time, an average of 18 mm of sediments were accreted above the horizon markers translating to ~9 mm yr-1 of accretion, a rate larger than both the current global rates of sea-level rise (~3.1 mm yr-1) and local measured rates of sea-level rise (3.8 mm yr-1) in Mombasa, a tide-gauge station nearest (~100 km) to the study site. Cumulatively, sediment elevation changes in Vanga indicate that they are outpacing the current rates of sea-level rise. However, they could be vulnerable to predicted and accelerated rates. It, therefore, calls for more holistic management and monitoring of the dynamics within the mangrove forests and adjacent terrestrial hinterlands.